Tidyroom XR: Extended Reality (XR) Based 3D Bedroom Interior Design Game Using Oculus Quest 2 - Mohammad Ikbaar Ath Thoriq; Cindy Taurusta; Nuril Lutvi Azizah; Novia Ariyanti (International Journal on Human-Computing Studies, 2026)
The advancement of Extended Reality (XR) technology, which includes Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR), has created fresh possibilities in multiple areas, such as interior design. This research seeks to create TidyRoom XR, a 3D game for bedroom interior design utilizing XR on the Oculus Quest 2, allowing users to engage directly inside a virtual space. The development process utilizes the Multimedia Development Life Cycle (MDLC) approach, which includes six phases: concept, design, resource gathering, production, evaluation, and distribution. The main goal of this application is to offer a helpful tool for interior designers and general users to visualize and organize bedroom layouts efficiently and precisely. Moreover, the application aims to provide a very engaging experience for creating bedrooms in a virtual setting. The test results reflected favorable results, indicating that the system functioned as intended, featuring an intuitive interface and responsive interactions. The game includes functions for object manipulation like Add, Move, Rotate, Drag, Drop, and Delete, and has two kinds of bedrooms furnished with typical items such as beds, tables, chairs, wardrobes, and drawers. These outcomes indicate that TidyRoom XR can function both as an effective platform for investigating interior design and as an interactive educational resource.